PROFIL SISWA SMP DALAM PEMECAHAN MASALAH YANG BERKAITAN DENGAN LITERASI MATEMATIS DITINJAU DARI ADVERSITY QUOTIENT (AQ) - Rahmawati, Novia Dwi; Mardiyana, Mardiyana; Usodo, Budi (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research aims to describe the profile of junior high school students with climberâs, camperâs, and quitterâs type in problem solving from related with mathematics literacy using Polya steps. This research was a qualitative descriptive research. The subjects of this research were taken by using a combined technique of stratified sampling and Snowball sampling. The subjects of this research were seven 9th grade students of SMP Negeri 6 Surakarta regency, which consisted of three students with climberâs type, two students with camperâs type, and two students with quittersâs type. The data were collected through questionnaire and task-based interview technique on subject matter of space and shape mathematics literacy third level. The data were analyzed using a Miles and Hubermanâs concept, that was data reduction, presentation, and conclusion. The results of this research are as follows: (1) climberâs students in understanding the problem, devising a plan, carrying out the plan, and looking back the answer aspects have reached all aspects needed, those are reasoning, argumentation, communication, modelling, connection, and representation aspect; (2) camperâs students in understanding the problem, devising a plan, and looking back the answer aspects have reached all aspects, those are reasoning, argumentation, communication, modelling, connection, and representation aspect, but in carrying out the plan, they have only reached reasoning, argumentation, communication, modelling and connection aspects, not representation aspect; (3) quitterâs students understanding the problem and looking back the answer aspects have reached all aspects, those are reasoning, argumentation, communication, modelling, connection, and representation aspect, but in devising a plan, they have only reached communication, modelling, and connection aspects, not reasoning, argumentation, and representation aspect. Whereas in carrying out the plan, they have only reached reasoning, argumentation, communication, modelling and connection aspects, not representation aspect.Keywords: Profile, problem solving, mathematics literacy, Polyaâs steps, Adversity Quotiont (AQ)Â